MENINGKATKAN MOTORIK HALUS PADA ANAK USIA 4-6 TAHUN - Sapitri, Dani; Basri, Hasan (DEVOSI, 2020)
At an early age is a very important and decisive age for child development. Early childhood is often referred to as the "golden age" or the golden age. At this time, almost all potential children experience a sensitive period to grow and develop rapidly and greatly. The development of each child is not the same because each individual has different developments. Early childhood is a time full of important and unique events that lay the foundation for a person's life in adulthood. The method of implementation carried out in carrying out Community Service activities is coloring, cutting the patterns that have been provided, folding origami paper and then sticking it on HVS paper and playing lego. Based on the results of teaching activities to improve fine motor skills in children aged 4-6 years at Raudathul Atfal Islamic Kindergarten, children can understand instructions from the presenters to color, cut, fold and play lego. The children also enjoy the material that has been done, and the children take part in the activities as the speaker has demonstrated